2000
DOI: 10.1007/s004150070151
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoglycanopathies in Dutch patients with autosomal recessive limb girdle muscular dystrophy

Abstract: Within a group of 76 sporadic/autosomal recessive limb girdle muscular dystrophy (LGMD) patients we tried to identify those with LGMD type 2C-E. Muscle biopsy specimens of 40 index patients, who had 22 affected sibs, were analyzed immuno-histochemically for the presence of three subunits: alpha-, beta-, and gamma-sarcoglycans. Abnormal sarcoglycan expression was established in eight patients, with six affected sibs. In one patient gamma-sarcoglycan was absent, and both alpha- and beta-sarcoglycans were reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 34 publications
1
30
0
2
Order By: Relevance
“…In the present study, carried out in a sample population composed exclusively of children, we showed that it seems to be the second more frequent, after sarcoglycanopathies. In other studies, including some conducted in Brazil, it was also shown that sarcoglicanopathy is the most common form, particularly when taking into account more severe forms of the disease and forms with earlier onset 13,14 . In a study carried out by a European consortium in 2005 by Saenz et al 15 , which included 484 LGMD patients from different geographic regions, screening for CAPN3 mutations was positive in approximately 50% of cases.…”
Section: Discussionmentioning
confidence: 88%
“…In the present study, carried out in a sample population composed exclusively of children, we showed that it seems to be the second more frequent, after sarcoglycanopathies. In other studies, including some conducted in Brazil, it was also shown that sarcoglicanopathy is the most common form, particularly when taking into account more severe forms of the disease and forms with earlier onset 13,14 . In a study carried out by a European consortium in 2005 by Saenz et al 15 , which included 484 LGMD patients from different geographic regions, screening for CAPN3 mutations was positive in approximately 50% of cases.…”
Section: Discussionmentioning
confidence: 88%
“…This apparent discrepancy may be alleviated by the fact that SGCA is expressed almost exclusively in skeletal muscle, SGCB must therefore be part of a unique sarcoglycan complex in myocardium and SGCB mutations may thus affect heart and skeletal muscle transcripts differently (Barresi R et al, 2000;Coral-Vazquez R et al, 1998;Crosbie RH et al, 2002). Chest pain reported by our patients can be caused by a vascular dysfunction previously reported for sarcoglycanopathies (Ginjaar HB et al, 2000).…”
Section: Discussionmentioning
confidence: 55%
“…In DMD, a disruption of the dystrophin-glycoprotein complex (DGC) causes the loss of a functional link between the cytoskeleton of myofibers and their extracellular matrix and may induce a secondary severe reduction of all sarcoglycans (Lim LE et al, 1995;Ginjaar HB et al, 2000). A primary defect in any of the sarcoglycan genes can lead to either total or partial loss of that protein as well as a secondary deficiency of the other sarcoglycans in the sarcolemma, possibly through a posttranslational effect (Durbeej JR et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The observation of cases in Mediterranean region (Libya, Jordan, Libanon, Saudi Arabia, Tunisia, etc. ) and now in Niger can be explained by migration flows in this area (BenHamida et al, 1983;Urtasun et al, 1998;Ginjaar et al, 2000;Merlini et al, 2000;Khadilkar et al, 2009). The line between Touaregs and arabo-berbers is now well established; then it is not surprising to observe the Delta 525T mutation in this ethnic group.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, many types of muscular diseases are known, based on their clinical and histopathological aspects, and the molecular bases of most of them are elucidated (Weiler and al., 1999;Leturcq and Kaplan, 2000;Urtizberea, 2001;Authier et al, 2008). A particular interest in investigating these pathologies was raised in developed countries around 1980 following the era of advances in molecular genetics (Gilchrist and al., 1988;Beckmann et al, 1991;Ginjaar et al, 2000;Sandona and Betto, 2009). It has been shown that these pathologies derive from anomalies in proteins involved in muscle cell structures or functions.…”
Section: Introductionmentioning
confidence: 99%